2021
DOI: 10.4111/icu.20200601
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance in males with low- to intermediate-risk localized prostate cancer: A modern prospective cohort study

Abstract: Purpose To compare the clinical outcome of males with low-risk and favorable intermediate-risk prostate cancer managed within a standardized modern protocol of active surveillance. Materials and Methods This was a prospective cohort study with strict and expanded active surveillance criteria in males with prostate cancer. Baseline assessment included multiparametric magnetic resonance imaging (mpMRI), extended systematic biopsy, and software-based MR-targeted biopsy. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…9) relative to LR patients. Among the studies (n = 4) that compared the risk of PCa death in LR and IR patients, there were no PCa-related deaths in either group [26][27][28]31]. Allcause deaths were assessed in two studies [28,31].…”
Section: 6mentioning
confidence: 99%
See 2 more Smart Citations
“…9) relative to LR patients. Among the studies (n = 4) that compared the risk of PCa death in LR and IR patients, there were no PCa-related deaths in either group [26][27][28]31]. Allcause deaths were assessed in two studies [28,31].…”
Section: 6mentioning
confidence: 99%
“…Among the studies (n = 4) that compared the risk of PCa death in LR and IR patients, there were no PCa-related deaths in either group [26][27][28]31]. Allcause deaths were assessed in two studies [28,31]. Rakauskas et al [31] recorded no deaths in their cohort, and Mukherjee et al [28] found a similar rate of all-cause death between LR (18/276) and IR (7/96) PCa patients with GG 2 (p = 0.8).…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, scrutinising against the selection criteria, 591 studies were excluded after reading the title or abstract, and 34 studies were excluded after full-text review. Ultimately, 25 studies were included in the systematic review [ 11 , 14 , 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…With all studies included, the chance of definitive treatment was 24% higher for the intermediate group than the low-risk group. As there was a very large difference for one study [ 30 ], the analysis was repeated with this study omitted. The results were not greatly changed by the omission of this study.…”
Section: Resultsmentioning
confidence: 99%